Analisis Kesalahan Berbahasa pada Teks Editorial dalam Modul Ajar Bahasa Indonesia Kelas XII SMA Kurikulum Merdeka - Renny Puspitasari; Elvienchi Multya Dewi; Trista Etika Putri; Prasasti Asadiva; Asep Purwo Yudi Utomo; Iwan Hardi Saputro (Student Research Journal, 2023)
Language has an important contribution in communicating with others. If there is no language for communication, it is impossible to run smoothly. The use of language cannot be separated from mistakes in both speech and writing. Language errors are forms of errors in the use of speech forms of various linguistic units in the form of words, sentences, and paragraphs. The standard language rule system is a form of Indonesian language rule that is used as a reference standard. The purpose of this investigation is to be able to describe the forms of language errors, the factors that trigger language errors, and efforts to resolve these errors. In the editorial text in the teaching module there are still language errors at the syntactic level, therefore it is interesting for the author to investigate errors at the syntactic level. In this research, we used two methods of data collection and data analysis. The data analysis method used was documentary. Apart from that, the descriptive method was used for analyzing data. From the data, it was found that there was an error in the language at the syntactic level in the editorial for the Indonesian language teaching module for class XII SMA Merdeka curriculum. Based on the data investigation conducted, there were 4 language errors found, among others, standard word errors, conjunction errors, punctuation errors, and effective sentence errors. The benefits obtained after conducting an analysis of language errors in editorial texts are improving sentence structure according to linguistic rules